2019
DOI: 10.1111/jocs.14402
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium septicum aortitis: A kiss of the devil

Abstract: Background: Clostridium septicum aortitis is a lethal infection. C. septicum has a strong association with an underlying malignancy, most commonly in the colon.Aim: Early identification methods and management strategies of C. Septicum infection. Materials and Methods:We present a 64-year-old man with aortic aneurysm and C.septicum bacteremia with unknown malignancy who passed away on the fourth day of hospitalization despite emergent endovascular intervention. Computed tomography showed periaortic gas which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…Interestingly, the individual inhibitory activity of clindamycin proved to be more effective (MIC 0Á08 µg ml −1 ) in comparison to the inhibitory activity of the penicillin in combination clindamycin (0Á63 µg ml −1 ). A recent study (Ranchal et al 2020), recommends that the combination should be used for the treatment of C. septicum which contradicts the in vitro activities observed herein. Ciprofloxacin has proven to be the most effective antibiotic with inhibitory (MIC 0Á08 µg ml −1 ) and bactericidal activity (MBC 0Á63 µg ml −1 ) observed against both Clostridial strains tested.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Interestingly, the individual inhibitory activity of clindamycin proved to be more effective (MIC 0Á08 µg ml −1 ) in comparison to the inhibitory activity of the penicillin in combination clindamycin (0Á63 µg ml −1 ). A recent study (Ranchal et al 2020), recommends that the combination should be used for the treatment of C. septicum which contradicts the in vitro activities observed herein. Ciprofloxacin has proven to be the most effective antibiotic with inhibitory (MIC 0Á08 µg ml −1 ) and bactericidal activity (MBC 0Á63 µg ml −1 ) observed against both Clostridial strains tested.…”
Section: Discussioncontrasting
confidence: 71%
“…When reviewing the antibiotic susceptibility against clostridial isolates it was found that of the fourteen antibiotics tested against C. perfringens, resistance was observed against eight antibiotics (Khan et al 2019). Another study recommended that a combination of clindamycin and penicillin should be used to treat C. septicum (Stevens et al 2005;Ranchal et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. septicum is a major etiological agent of nontraumatic or spontaneous gas gangrene, a fulminant form of myonecrosis, in humans (38). The incidence and epidemiology of C. septicum infection in humans is unknown; however, on the basis of case reports, the bacterium can cause aortitis (53)(54)(55)(56)(57)(58), pneumorachis (59,60), meningitis (61), and hepatic abscess (62). These infections can lead to gas gangrene, and even septicemia, with a mortality rate of up to 79% within 48 hours (34).…”
Section: Discussionmentioning
confidence: 99%
“…A review of all reported cases of C. septicum aortitis demonstrated this to be the 73rd reported case. [2][3][4][5][6][7] C. septicum is a Gram-positive, spore-forming rod, with a strong predisposition to spread throughout the body both via local and haematogenous distribution. 8 Aortic involvement is associated with colonic carcinoma in up to 56%, 2 as its anaerobic growth is facilitated by the hypoxic, necrotic milieu of the tumour.…”
mentioning
confidence: 99%